Chiral Phosphoric Acid Catalyzed Enantioselective [4+3]-Cyclization Reaction of Indol-4-ylmethanols and Quinone Esters - Chen, Zhouli; Wang, Lei; Qian, Yiheng; Lin, Xufeng (Synlett, 2021)
An asymmetric [4+3]-cyclization reaction of racemic indol-4-ylmethanols and quinone esters catalyzed by chiral phosphoric acids has been developed. This method provides efficient access to biologically important [1]benzoxepino[5,4,3-cd]indoles featuring both axial and central chirality in good yields and up to 98% ee, as essentially single diastereomers, under mild reaction conditions.
Keywords: chiral phosphoric acids; [4+3]-cycloaddition; asymmetric catalysis; indoles; quinones; benzoxepinoindoles